THE ENREDO DO BRASIL - 1st ACT. - Rosa Maria Godoy Silveira (Clio: Revista de Pesquisa Histórica, 2002)
This article deals with a study on the Independence and Formation of the Brazilian Nation, including the role of the private sector as an auxiliary of the State, with regard to changes in the infrastructure and different ways of achieving the interiorization of the Metropolis, as well as , shows the opposite movement: the Colony in the Kingdom.